1985
DOI: 10.1073/pnas.82.8.2478
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically activated steviol, the aglycone of stevioside, is mutagenic.

Abstract: Stevioside, a constituent of Stevia rebaudiana, is commonly used as a noncaloric sugar substitute in Japan. Consistent with reports in the literature, we have found that stevioside is not mutagenic as judged by utilization of Salmonella typhimurium strain TM677, either in the presence or in the absence of a metabolic activating system. Similar negative results were obtained with several structurally related sweet-tasting glycosides. However, steviol, the aglycone of stevioside, was found to be highly mutagenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 27 publications
(33 reference statements)
1
64
0
5
Order By: Relevance
“…The results were shown in Table 1 as their specific mutation ratio (mutation frequency/mg sample/ plate). Steviol indicated almost similar levels of mutagenicity under the presence of S9 mixture, as reported by Pezzuto et al 6) or Matsui et al 8) Of the eight synthesized derivatives, four compounds [steviol-16,17-epoxide (3), steviol methylester (6), 13,16-seco-13-oxo-steviol methylester (8), and steviol methylester 8,13-lactone (10)] were found to be mutagenic at nearly the same level as steviol (2) itself only under the presence of S9 mixture, and the other three compounds has no activity since over the detection limit. Regardless of the presence or absence of the rat liver ribosomal fraction, 15-hydroxy steviol (4), 16-oxo-steviol methylester (7) and 3,16-seco-13-hydroxy-steviol methylester (9) were found to be non-mutagenic or below detection limit in the test system.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The results were shown in Table 1 as their specific mutation ratio (mutation frequency/mg sample/ plate). Steviol indicated almost similar levels of mutagenicity under the presence of S9 mixture, as reported by Pezzuto et al 6) or Matsui et al 8) Of the eight synthesized derivatives, four compounds [steviol-16,17-epoxide (3), steviol methylester (6), 13,16-seco-13-oxo-steviol methylester (8), and steviol methylester 8,13-lactone (10)] were found to be mutagenic at nearly the same level as steviol (2) itself only under the presence of S9 mixture, and the other three compounds has no activity since over the detection limit. Regardless of the presence or absence of the rat liver ribosomal fraction, 15-hydroxy steviol (4), 16-oxo-steviol methylester (7) and 3,16-seco-13-hydroxy-steviol methylester (9) were found to be non-mutagenic or below detection limit in the test system.…”
Section: Resultssupporting
confidence: 71%
“…4) However, it is known that stevioside is converted to its aglycone, steviol, by intestinal bacteria when orally administered to rats. 5) Pezzuto et al 6) demonstrated that steviol causes a dose-dependent positive response in the forward mutation assay using S. typthimurium TM677 in the presence of a metabolic activation system (Aroclor-induced rat liver S9 fraction).…”
Section: Steviosidementioning
confidence: 99%
“…Infrared spectra were acquired with a Perkin-Elmer FT-IR 1600 spectrometer using KBr for solids and film for liquid samples (range 4000-400 cm -1 ). 1 H NMR (200 MHz) and 13 C NMR (50 MHz, fully decoupled) spectra were recorded with a Bruker AC-200F spectrometer. Samples were prepared in CDCl 3 solution containing 1-2% tetramethylsilane (TMS) as internal standard.…”
Section: General Considerationsmentioning
confidence: 99%
“…6 Kaurenoic acid (1), along with several related kauranes, 7 exhibits a wide variety of biological activities such as antimicrobial, anti-inflammatory, anti-fertility, cytotoxic, and trypanocidal. [8][9][10][11][12][13][14][15][16] The relatively high natural abundance of kaurenoic acid (1) and the inexistence of a general method for the synthesis of alkyl kaurenoates by esterification of 1 provides further motivation to investigate its chemical modification 17 in order to obtain derivatives and test their pharmacological activity. 18 This paper describes a general synthesis of kaurenoic esters and derivatives as well as their antifungal activity, evaluated against a panel of human opportunistic pathogenic fungi including yeasts, hialohyphomycetes and dermatophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Stevioside was isolated from a 1-butanol-soluble extract of S. rebaudiana by absorption column chromatography (Kinghorn and Soejarto, 1991). Steviol (molecular weight = 804.80) was obtained by enzymatic hydrolysis of stevioside with pectinase (Pectinol 50 L, Corning Biosystems) (Pezzuto et al, 1985).…”
Section: Methodsmentioning
confidence: 99%